Multifunctional resource room teacher training and enactment with the diversity of the target population of special education - de Oliveira, Anna Augusta Sampaio [UNESP]; Prieto, Rosângela Gavioli (FapUNIFESP (SciELO), 2020)
The changes implemented in Brazil related to inclusive education and Specialized Educational Service (SES) have substantial effects on teacher performance in Multifunctional Resource Rooms (SRM), as it is now necessary to work with all categories of the target population of Special Education. Thus, this research aimed to analyze the training and enactment of teachers of the Municipal Education Network of São Paulo. As a data collection procedure, an electronic questionnaire was used through Google Docs, sent to 400 teachers of these classrooms, from which we obtained a return of 179 (45%). After the collection, data were analyzed through Atlas.ti 8.4-14 Software for Windows. The results indicated that 150 teachers (84%) did not feel able to work with all categories of the target population of Special Education and 29 (16%) said they did. In addition, teachers were invited to comment on their responses and of the 179 respondents, 81 (45%) provided justifications related to their work experience in their training areas, 61 (34%) mentioned the need for professional improvement, 28 (16%) commented that they have training in only one or a few of the categories they worked with, 5 (3%) referred to their work experience and 4 (2%) referred to intersectority. The analysis of the data allows us to affirm that there is a significant distance between training and enactment with all the diversity of the target population of Special Education, bringing substantial difficulties to the pedagogical practice.
Formação de professores das salas de recursos multifuncionais e atuação com a diversidade do público-alvo da educação especial
Keywords: Inclusive education; Special Education; Teacher training